2001
DOI: 10.1016/s1388-2457(01)00516-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of task-related ipsilateral hand movement on motor cortex excitability

Abstract: Objective: The time course of the right motor cortex excitability in relation to a task-related voluntary right thumb twitch was studied using sub-threshold transcranial magnetic stimulation (TMS) to the right motor cortex.Methods: Motor excitability was studied in 8 adult subjects who made a brief right thumb twitch to the predictable omission of every ®fth tone in a series of tones 2.5 s apart. This paradigm avoided an overt sensory cue, while allowing experimental control of TMS timing relative to both move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Even viewing a mirror image of the ipsilateral hand has been found to excite the ipsilateral M1 pathway (9), as can simple finger movements (20). In contrast, some studies have also suggested that both inhibition and excitation may be present owing to unilateral movement (26,32). A recent review by Carson (6) assesses the means by which excitatory and inhibitory interactions take place at multiple levels of the neuraxis during unilateral and bilateral tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Even viewing a mirror image of the ipsilateral hand has been found to excite the ipsilateral M1 pathway (9), as can simple finger movements (20). In contrast, some studies have also suggested that both inhibition and excitation may be present owing to unilateral movement (26,32). A recent review by Carson (6) assesses the means by which excitatory and inhibitory interactions take place at multiple levels of the neuraxis during unilateral and bilateral tasks.…”
Section: Discussionmentioning
confidence: 99%
“…We used an experimental design similar to the one we used in a study of ipsilateral motor excitability during movement [34] that avoids an overt sensory cue, while allowing experimental control of TMS timing relative to both the movement and the cue to move. Sub-threshold TMS was employed to study the time course of motor excitability that was measured by probability of activating motoneurones (MEP probability) and by the degree of motor activation (MEP amplitude) to reveal both excitatory and inhibitory effects.…”
Section: Introductionmentioning
confidence: 99%
“…This protocol assured that subjects could neither predict nor adapt to the disturbance. Haptic parameters were adjusted to avoid overlap of EEG signals related to cognitive or visual processing associated with the beginning of the trial [8,15]. Specifically, haptically rendered virtual table stiffness, static and dynamic friction, and environment viscosity were tuned in the experimental software, based on the preliminary pilot tests.…”
Section: Methodsmentioning
confidence: 99%